Enterprise Risk Management and Corporate Governance Effect Towards Sustainability and Performance Moderated by Market Crash - Dwityas Adi Kusumo Wardoyo; Saifi, Muhammad; Imamah, Nur (FIA UB, 2024)
The COVID-19 crisis has significantly impacted the global economy, instantly triggering an effect on stock market stability forcing companies to adapt to the uncertainty of economic conditions to survive. Implementing enterprise risk management (ERM), corporate governance (CG), and sustainability can help companies improve or maintain their performance. Companies faced the prospect of a stock market crash amid the crisis' chaos. This study aims to analyze the effect of ERM, CG, and sustainability on performance moderated by market crashes in companies listed on the LQ45 Index Indonesia Stock Exchange (IDX) during the 2020 period when the composite stock price index (IHSG) crashed. Thirty-three companies served as the study's samples, while secondary data from partial least squares (PLS) and descriptive analysis were employed. The findings suggest that ERM and CG have a significant impact on sustainability and also have an insignificant impact on performance. Furthermore, sustainability has a significant effect on performance, and market crashes have a moderating effect that improves the impact of ERM on performance.